2022
DOI: 10.3390/life12101556
|View full text |Cite
|
Sign up to set email alerts
|

Two-Year Follow-Up on Chemosensory Dysfunction and Adaptive Immune Response after Infection with SARS-CoV-2 in a Cohort of 44 Healthcare Workers

Abstract: Persistent chemosensory dysfunction (PCD) is a common symptom of long-COVID. Chemosensory dysfunction (CD) as well as SARS-CoV-2-specific antibody levels and CD8+ T-cell immunity were investigated in a cohort of 44 healthcare workers up to a median of 721 days after a positive PCR test. CD was assessed using questionnaires and psychophysical screening tests. After 721 days, 11 of 44 (25%) participants reported PCD, with five describing an impaired quality of life. One participant reported hyperosmia (increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 71 publications
0
9
0
Order By: Relevance
“…30,31 In line with what observed in the present investigation, four independent studies reported the prevalence and recovery rate of self-reported chemosensory dysfunction 2 years after SARS-CoV-2 infection with figures ranging from 8% to 30%, and from 60% to 87%, respectively. [32][33][34][35] However, only one study has evaluated the prevalence of OD 2 years after infection by means of psychophysical evaluation, observing a persistent smell dysfunction in 3% of cases. 33 This much lower rate of OD compared to that observed in the present study may at least in part be due to the fact that only an orthonasal odor identification test was performed.…”
Section: Discussionmentioning
confidence: 99%
“…30,31 In line with what observed in the present investigation, four independent studies reported the prevalence and recovery rate of self-reported chemosensory dysfunction 2 years after SARS-CoV-2 infection with figures ranging from 8% to 30%, and from 60% to 87%, respectively. [32][33][34][35] However, only one study has evaluated the prevalence of OD 2 years after infection by means of psychophysical evaluation, observing a persistent smell dysfunction in 3% of cases. 33 This much lower rate of OD compared to that observed in the present study may at least in part be due to the fact that only an orthonasal odor identification test was performed.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in animals associated these symptoms with viral persistence and inflammation in the olfactory epithelium ( 58 ), but the underlying mechanisms of these persistent dysfunctions are still debated ( 19 ). Recent studies have started to explore the involvement of humoral responses in systemic ( 59 , 60 ) and mucosal compartments ( 24 ). In accordance with their results, we did not observe a major difference in serum IgA regarding the duration of olfactory symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in animals associated these symptoms with viral persistence and inflammation in the olfactory epithelium (51), but the underlying mechanisms of these persistent dysfunctions are still debated (19). Recent studies have started to explore the involvement of humoral responses in systemic (52, 53) and mucosal compartments (24). In accordance with their results, we did not observe a major difference in serum IgA regarding the duration of olfactory symptoms.…”
Section: Discussionmentioning
confidence: 99%